(untitled) (Heritage, 2023)
In the spring of 1972, the infectious disease smallpox appeared in Yugoslavia, which was characterized by high mortality. Today, it is known for certain that the epidemic was brought by Ibrahim Hoti, a pilgrim who went on a trip to Saudi Arabia and Iraq. Most of the sick and deceased were from the area of the then Socialist Autonomous Province of Kosovo, followed by those from Belgrade. On the territory of the municipality of Kraljevo during the smallpox epidemic, there were no cases of infection, although the areas where the infections appeared are geographically very close. Nikola Nakaradić, a student of the Forestry High School and a resident of the boarding school in Kraljevo, was one of those infected and successfully cured. He got the symptoms and the diagnosis when he was not in Kraljevo, and then he was treated and taken care of in a quarantine in Belgrade, which is why he was listed as a patient from Belgrade in the records. Getting out of the epidemic situation without a single case of illness in the area of the then municipality of Kraljevo is considered a success, especially considering the poor state of healthcare, both in terms of material and technical conditions, and in terms of unpreparedness for the challenge of a sudden epidemic. The municipal headquarters for quarantine diseases carried out combat measures by organizing quarantines, and mass vaccination of the population was carried out. The quick formation of the quarantine, immediately after learning that the resident of the boarding school was infected, as well as the quick and successful action to locate the fugitives from the quarantine, represent the merit of the internal affairs authorities, while the greatest merit certainly belongs to the health care workers, on whose shoulders fell the main burden of responsibility and who engaged in preventing the virus outbreak in Kraljevo The fact that Nikola Nakaradić from Morović, a sick student of the Forestry School and a resident of the boarding school in Kraljevo, did not infect anyone in the territory of Kraljevo can certainly be considered an extremely fortunate set of circumstances. Unfortunately, material conditions in the health institutions in Kraljevo did not significantly improve even several years after the epidemic. The experience of smallpox has led to the fact that in the next draft of the health care program, measures for the detection, prevention, control and treatment of infectious diseases will be outlined in the first point. The formal legal basis has been laid, but experience after smallpox has shown that the action in the first moments of the epidemic is the most important. Knowledge, conscientiousness, responsibility, courage and dedication of health workers and other employees in competent institutions are the first and most important frontline for preventing epidemics at their very beginnings.